The evolution and performance of the Henderson Mine’s C-arch shotcrete drawpoint support - Shea, NA (Ground Support 2019: Ninth International Symposium on Ground Support in Mining and Underground Construction, 2019)
For over 30 years, the Henderson Mine used varying styles of steel and concrete drawpoint support in its panel caving operation. In 2007, a radical departure from the traditional brow was first tested. This ‘C-arch’ drawpoint was built with shotcrete and used cable bolts to secure the in situ rock to act as a brow. This dramatic change was a major reduction in the effort and materials required to build the drawpoint, but time was required to understand the performance under draw conditions. Based on the performance of the first few test drawpoints, the C-arch was used in the final portion of the 7210 Main production panel with positive results. Subsequently, the current production panel, known as the 7700 Southwest (SW) panel, was developed entirely with C-arch drawpoints. Midway through the development of the 7700 SW panel, the C-arch design was updated. This update simplified the surface support installation to improve the efficiency and quality of the surface support. The 7700 SW panel is now in a fully mature stage of production. Data has been collected on the wear characteristics of nearly 200 drawpoints on the panel over several years. This provides the first opportunity for analysis of the performance of the C-arch across a full production panel, from cave initiation to maturity. Data analysis provides insight into factors that influence the wear performance of the C-arches. In addition, the data supports the design change made mid-panel, and the continued use of C-arches for drawpoint support.
Keywords: ground support; drawpoint; brow; extraction level